(untitled) (Research, Society and Development, 2024)
Objective: To report a clinical case about the use of orthodontic aesthetic aligners in the treatment of relapse of lower anterior dental crowding, based on a literature review. Methodology: This is a descriptive analytical clinical case report carried out at the NEO ODONTOLOGIA teaching clinic in Maceió - AL, in the specialization course in orthodontics, based on the patient’s permission through the Free and Informed Consent Form to share her images for the purpose of this study. Case report: Patient R.S.F.F., female, 24 years old, leucoderma, sought the specialization course in orthodontics with the main complaint of "aligning her teeth". During the anamnesis, the patient reports having previously undergone orthodontic treatment, but notes relapse of crowding in the lower anterior region and seeks quick and more aesthetic treatment. Conclusion: Aesthetic orthodontics involving aligners, indicated for the treatment of lower anterior crowding in patients with relapse, as an alternative treatment, proved to be a favorable and effective indication for the correction of malocclusion, associated with good planning and execution, combined with technological tools and patient cooperation.